Low-to-Moderate-Intensity Resistance Exercise Effectively Improves Arterial Stiffness in Adults: Evidence From Systematic Review, Meta-Analysis, and Meta-Regression Analysis - Zhang, Yong; Zhang, Ya-Jun; Ye, Weibing; Korivi, Mallikarjuna (Frontiers in Cardiovascular Medicine, 2021)
Background/Purpose: Resistance exercise (RE) is known to improve cardiovascular health, but the role of RE variables on arterial stiffness is inconclusive. In this systematic review and meta-analysis, we investigated the influence of RE and its intensities on arterial stiffness measured as pulse wave velocity (PWV) in young and middle-aged adults. Methods: Web of Science, PubMed/MEDLINE, Scopus, EMBASE, Cochrane Library, ScienceDirect, CINAHL, Wiley Online Library and Google Scholar were searched for relevant studies. RE trials that reported PWV data, and compared with respective controls were included. Cochrane Collaboration tool was used to assess the risk of bias. Results: Data were synthesized from a total of 20 studies, involving 981 participants from control (n=462) and exercise (n=519) trials. The test for overall effect (pooled outcome) showed RE intervention had no effect on arterial stiffness (SMD=-0.09; 95% CI:-0.32, 0.13; P=0.42), but risk of heterogeneity (I2) was 64%. Meta-regression results revealed a significant correlation (P=0.042) between RE intensity and PWV changes. Consequently, the trials subgrouped into high-intensity and low-to-moderate-intensity to identify the effective RE intensity. Subgroup analysis showed that low-to-moderate-intensity significantly decreased PWV (SMD=-0.34; 95% CI:-0.51, -0.17; P<0.0001), while high-intensity had no effect (SMD=0.24; 95% CI:-0.18, 0.67; P=0.26). When trials separated into young and middle-aged, low-to-moderate-intensity notably decreased PWV in young (SMD=-0.41; 95% CI:-0.77, -0.04; P=0.03) and middle-aged adults (SMD=-0.32; 95% CI:-0.51, -0.14; P=0.0007), whereas high-intensity had no effect in both age groups. Conclusions: Our findings demonstrated that RE intensity is the key variable in improving the arterial stiffness. Low-to-moderate-intensity can prescribe as an effective non-pharmacological strategy to treat cardiovascular complications in young and middle-aged adults.